Neurosensorimotor Reflex Integration in Children with Special Needs and Developmental Delays : A Qualitative Study - Muhajir Muhajir; Nurwalmi Nurwalmi; Sri Rejeki Syamsuryah; Zil Mutadayyanah; Darwis Durahim; Syamsuddin Syamsuddin (Proceeding of The International Conference on Economics and Business, 2024)
Children with special needs (CSN) often face challenges in accessing education, healthcare, and social participation. Physiotherapy can be an effective intervention to help CSN reach their full potential. Neurosensorimotor Reflex Integration (NSRI) is a structured intervention approach that aims to promote the integration and maturation of the nervous system in CSN. Objectives: This study aimed to explore the experiences and perspectives of parents and therapists regarding the effectiveness of NSRI in improving the motor, sensory, and cognitive skills of CSN. Methods: A qualitative study was conducted using a phenomenological approach. Data were collected through in-depth interviews and observation with 10 participants (6 parents and 4 physiotherapists). Results: Participants reported positive outcomes following NSRI intervention, including improvements in motor skills, sensory processing, and attention regulation. The individualized and holistic nature of NSRI was appreciated by both parents and therapists. Conclusion: NSRI may be a promising therapeutic approach for a wide range of special needs. More research is needed to determine the optimal dosage and duration of NSRI intervention.